The role of satisfaction in mediating the effect of perceived ease of use and perceived usefulness on purchase intention: Study on Bukalapak marketplace’s customer in Bali Province - Asmarina, Ni Luh Putu Gede Maharupa; Yasa, Ni Nyoman Kerti; Ekawati, Ni Wayan (International research journal of management, IT and social sciences, 2022)
The purpose of this study is to examine and explain the role of satisfaction in mediating the effect of perceived ease of use and perceived usefulness on the repurchase intention of Bukalapak marketplace users in Bali. The research subjects were users of the Bukalapak marketplace with a total sample of 140 respondents who had the criteria of having a high school/vocational high school education level, domiciled in Bali, and had shopped using the Bukalapak marketplace. The data were analyzed using the SEM-PLS technique with the Smart PLS version 3.0 application. The results show that all research hypotheses are supported. Practical implications based on research findings show that among the three variables that influence repurchase intention, the satisfaction variable has the highest path coefficient which can be a reference for Bukalapak management in making marketing strategies to increase repurchase intention in Bukalapak customers by increasing satisfaction.